2018
DOI: 10.1097/md.0000000000011004
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of PD-L1 expression in sarcoma

Abstract: Programmed cell death-ligands 1 (PD-L1) is a key immune checkpoint protein and a promising therapeutic target for malignancy tumor immunotherapy. The prognostic value of PD-L1 in patients with bone and soft tissue sarcoma remains controversial. Therefore, this meta-analysis is conducted to evaluate the associations of PD-L1 expression with overall survival (OS), progression-free survival (PFS), and clinicopathological characteristics of sarcomaA comprehensive literature search of PubMed, Web of Science, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…The frequency of PD-L1 expression in sarcomas reported in the literature is highly variable with incidences ranging from 0% to 65% [5,[7][8][9][10][11][12][13][14][15][16][17][18][19]. In their analysis, some of these series have combined statistical analysis of the two molecularly characteristic groups of sarcomas, that is those associated with recurrent specific genetic events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of PD-L1 expression in sarcomas reported in the literature is highly variable with incidences ranging from 0% to 65% [5,[7][8][9][10][11][12][13][14][15][16][17][18][19]. In their analysis, some of these series have combined statistical analysis of the two molecularly characteristic groups of sarcomas, that is those associated with recurrent specific genetic events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We did not investigate the correlation between PD-L1 IHC expression and specific clinical pathological variables (i.e. tumour size, grade, site, patient's age, etc), as such correlation has not been previously identified (9,14) and no obvious trend was seen in our cohort (See Table 1 paediatric osteosarcomas, demonstrated that 75% of metastatic lesions but no primary osteosarcomas expressed PD-L1 (35). The same phenomenon was observed in a case of dedifferentiated chondrosarcoma, which showed absence of PD-L1 in the primary tumour and positive expression in the metastasis (36) and this has also recently been documented in a series of metastatic renal cell carcinomas (37).…”
Section: Discussionmentioning
confidence: 93%
“…Our other Rec/Met paired cases showed concordant absence of TILs at initial presentation and on the metastasis / recurrence ( Table 1). As high density TILs (specifically, CD3+/CD8+) is an independent positive prognostic factor for OS and DFS in sarcomas (10) We did not characterise subsets of TILs (ie.. CD8+, FoXP3+, etc) because this has been previously published (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and because our study focused on the possible relevance of TILs on histological H&E-stained sections. With regards to the correlation between PD-L1 and PD-1 expression this is conflicting with a study from the Cancer Genome Atlas Research Network demonstrating that PD-L1 mRNA does not correlate with PD-1 (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations